Inactivation of Escherichia coli by atmospheric pressure plasma jet in water. (2nd June 2022) - Bakhshzadmahmoudi, Mehdi; Morshedian, Nader; Mehramiz, Ahmad; Kharaghani, Manijeh
Abstract: The main aim of this work is inactivation of Escherichia coli in water using a laboratory-scale radio-frequency atmospheric pressure Argon plasma jet. This bacterium is widely present in the environment, especially in drinking water, and its pathogenic effects are very harmful. For this purpose, an Argon flow rate of 3.5 slm, maximum plasma power of 200 W, and discharge frequency of 13.56 MHz was conducted to generate a uniform plasma plume for water treatment. 150 ml of drinking water contaminated by E. coli was exposed to the radiation of plasma placed about 3 cm within the water, the treatment time varied from 2 to 6 minutes at 100, 150, and 200 W of plasma input power. The temperature of the plume, discharge current and voltage, and electron density were all measured to characterize the plasma. Active species such as excited molecules, ions, and radicals produced in the plasma in water were detected using the optical emission spectroscopy method. The decreasing behavior of live bacteria versus exposure time and plasma jet input power was observed, and finally, at the discharge power of 200 W and 6 min, an effective inactivation was achieved and the number of bacteria reduced from 92×10 4 to less than 1.7 MPN/100 ml. HIGHLIGHTS: Construction of a 200-W atmospheric pressure Argon plasma jet. Using a 13.56-MHz radio-frequency power supply for plasma generation. Treatment of water by a stable Argon plasma plume. Inactivation of Escherichia coli in water by plasma. Graphical Abstract